THE SYNERGISTIC EFFECTS OF PRODUCT QUALITY AND BRAND IMAGE ON CONSUMER SATISFACTION AND PURCHASE DECISIONS - Aam Halimtar; Asep Rokhyadi Permana Saputra (Journal of Management and Science, 2026)
The smartphone industry has experienced rapid growth and has become an integral part of modern lifestyles, serving not only as a communication tool but also as a reflection of personal identity. Although numerous studies have examined product performance and marketing strategies, the combined influence of product quality and brand image on purchase decisions, with customer satisfaction as a moderating variable, has not been extensively explored. This study aims to investigate these relationships among smartphone users in Yogyakarta, Indonesia. It is grounded in Expectation Confirmation Theory (ECT), which posits that satisfaction occurs when product performance meets or exceeds consumer expectations. A quantitative research design was employed using purposive sampling, involving 400 respondents obtained through online questionnaires. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4, including tests for validity, reliability, and hypothesis verification through bootstrapping. The findings reveal that product quality and brand image significantly and positively affect customer satisfaction and purchase decisions, while satisfaction further strengthens the influence of these two variables on consumer buying behavior. The results support ECT by emphasizing that both functional factors (product quality) and emotional factors (brand image) play crucial roles in shaping consumer decisions. From a managerial perspective, smartphone companies are advised to ensure consistent product quality and develop a strong brand image to meet consumer expectations and enhance satisfaction, which ultimately fosters purchase decisions and customer loyalty.